Additions to the knowledge of the diversity of saprobic conidial fungi of the cloud forest of Veracruz IV - Arias Mota, Rosa María; Heredia Abarca, Gabriela; Castañeda Ruiz, Rafael F. (Instituto de Ecología, A.C., 2015)
This work is part of a series of papers aiming to contribute to the knowledge of the conidial fungi species that proliferate in cloud forest remnants of the state of Veracruz. Twenty nine species are described and illustrated here. All of them are new records for Mexico.